Out-In Model Hybrid Learning Management in Improving Scientific Publications - H. Soro, Suharyanto; Komara, Endang; Fathoni, Khoirul; Witasari, Rinesti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to explore the ideal model of hybrid learning management to improve the scientific publication of Graduate School Students. The researcher uses a qualitative research paradigm with a case study approach. The data collection method uses observation, questionnaire, and interview methods. The sample in this study is Muslim Postgraduate students. Sample selection was carried out by purposive sampling. The sample number was 35 people consisting of 20 women and 15 men. This sample was chosen because (1) They are Muslims; (2) They come from the island of West Java (Subang, Sumedang, Bandung City, Bandung Regency, Purwakarta Regency); (3) They have the status of teachers. The researcher took a sample of research from second-semester students at the Graduate School of the Islamic University of Nusantara Bandung, West Java. Research activities will be carried out in the 2023-2024 academic year. The findings of the study show that (1) hybrid learning management can improve scientific publications by using the OUTIN model. The IN model refers to the lecture process on campus, while the OUT model refers to student activities in the field in the context of collecting research data. (2) Hybrid learning management is carried out in five stages, namely the identification, planning, implementation, evaluation, and follow-up stages; (3) Lecturers have different teaching styles and most graduate students respond positively with different percentage levels. The results of this research make a positive contribution to lecturers and students, especially for each course so that they can form a culture of writing and publishing the results of their thoughts in the form of journals or ISBN books so that they can increase the number of scientific publications.